PERKEMBANGAN LATISIFER PADA KULTUR KALUS CATHARANTHUS ROSEUS (L) G. DON YANG DIINDUKSI DENGAN KOMBINASI ZAT PENGATUR TUMBUH KINETIN + NAA - DARSINI, NI NYOMAN (Jurnal Biologi Udayana, 2011)
The development of laticifer on callus culture of Catharanthus roseus (L) G Don in Zenk medium supplemented with combination of plant growth regulator kinetin + NAA was studied. The explants were taken from the second folium from shoot apex. Development of laticifer was observed using descriptive analysis method for callus anatomy and percentage of laticifer was observed during 4–14 weeks of callus development. The percentage of laticifer was determined by counting the average number of the laticifer and the average number of surrounding cells in every optical field of few under light microscope. The results showed that early development of laticifer which was induced with plant regulator growth kinetin + NAA was found in the 9 weeks old callus. The laticifer has specific characteristics i.e. thicker cell wall and longer cell than sorounding cell. Elongated laticifer was observed at 12 weeks old callus. The highest percentage of laticifer on callus C. roseus induced with combination of kinetin and NAA was found in 12 weeks old callus i.e. 0,12%. At 13 and 14 weeks old callus, the anatomy of laticifer was similar to that at 12 weeks old callus, but the percentage was lower.
Keywords: callus; explant; kinetin; laticifer; NAA; Zenk medium